2018
DOI: 10.1055/s-0038-1636540
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant State in Current and Former Anabolic Androgenic Steroid Abusers

Abstract: Background Anabolic androgenic steroid (AAS) abusers are considered at increased risk of cardiovascular morbidity and mortality. We hypothesized that current and former AAS abuse would induce a procoagulant shift in the haemostatic balance. Methods Men 18 to 50 years of age were included as current AAS abusers, former AAS abusers or controls. Morning blood samples were collected after overnight fasting. Thrombin generation (lag time, time to peak, peak height, and endogenous thrombin potential [ETP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Subsequently, we reported reduced left ventricular ejection fractions and ventricular diastolic impairments in middle-aged long-term users of supraphysiologic-dose AAS (Baggish et al, 2010), effects that we and others confirmed in subsequent larger-scale studies (Angell et al, 2012;Luijkx et al, 2013;Baggish et al, 2017;Rasmussen et al, 2018a). Other groups also have reported finding right ventricular abnormalities (Angell et al, 2014;Alizade et al, 2016;Rasmussen et al, 2018a), apoptosisrelated fibrotic changes in the heart (Cecchi et al, 2017), increased systolic blood pressure and aortic stiffness (Rasmussen et al, 2018b), and a pro-coagulant state (Chang et al, 2018) in long-term supraphysiologic-dose AAS users. In an echocardiography study in male rabbits, 6 months of supraphysiologic nandrolone administration (SC, 4 or 10 mg/kg, twice/ week) was associated with impaired global myocardial performance in a dose-related manner (Vasilaki et al, 2016).…”
Section: Cardiovascular Abnormalities Associated With Supraphysiologisupporting
confidence: 77%
“…Subsequently, we reported reduced left ventricular ejection fractions and ventricular diastolic impairments in middle-aged long-term users of supraphysiologic-dose AAS (Baggish et al, 2010), effects that we and others confirmed in subsequent larger-scale studies (Angell et al, 2012;Luijkx et al, 2013;Baggish et al, 2017;Rasmussen et al, 2018a). Other groups also have reported finding right ventricular abnormalities (Angell et al, 2014;Alizade et al, 2016;Rasmussen et al, 2018a), apoptosisrelated fibrotic changes in the heart (Cecchi et al, 2017), increased systolic blood pressure and aortic stiffness (Rasmussen et al, 2018b), and a pro-coagulant state (Chang et al, 2018) in long-term supraphysiologic-dose AAS users. In an echocardiography study in male rabbits, 6 months of supraphysiologic nandrolone administration (SC, 4 or 10 mg/kg, twice/ week) was associated with impaired global myocardial performance in a dose-related manner (Vasilaki et al, 2016).…”
Section: Cardiovascular Abnormalities Associated With Supraphysiologisupporting
confidence: 77%
“…AAS can directly affect the coagulation/fibrinolysis system, [30] and abusers have an increased risk of arterial and intra-cardiac embolism and a higher incidence of deep vein thrombosis and pulmonary embolism. [31] These drugs enhance platelet generation and aggregation, which expand the range of thrombus embolism [32] and promote the generation of thrombin [33] and thromboxane A2 (TXA2), which inhibit the production of prostacyclin (prostaglandin I2, an inhibitor of platelet aggregation) and results in hyper-coagulability. [26,34] Additionally, testosterone directly regulates TXA2 receptor density on platelets and vascular cells, thus affecting the coagulation/fibrinolysis function.…”
Section: Effects Of Aas On the Cardiovascular Systemmentioning
confidence: 99%
“…On the other hand, a recent study of Madson et al found a higher odds for hematocrit levels >0.50 L/L for long-acting undecanoate intramuscular injections (2.9 95% CI 1.7-5.0) than for short-acting esters (1.1 CI 0.7-1.6), both compared to transdermal applications during a 20 year follow-up period (Madsen et al, 2021). At the level of the coagulation cascade, testosterone therapy in both cis and trans men, as well as in cis women, does not induce procoagulant changes (Agledahl et al, 2009;Anderson et al, 1995;Bland et al, 2005;Buckler et al, 1998;Chang et al, 2018;Scheres et al, 2021;Toorians et al, 2003).…”
Section: Vte Risk Of Virilizing Hormonal Therapymentioning
confidence: 99%